EFEKTIVITAS PLATFORM E-COMMERCE BERBASIS KOMUNITAS DALAM PENINGKATAN PEMASARAN DIGITAL UNTUK UMKM DI SULAWESI BARAT - Musyrifah, Musyrifah; Saal, Asmawati (J-Icon : Jurnal Komputer dan Informatika, 2024)
This study aims to measure the effectiveness of a community-based e-commerce platform in enhancing digital marketing for UMKM in West Sulawesi. UMKM often face significant challenges in reaching wider markets, mainly due to limitations in infrastructure, technology access, and digital marketing knowledge. DiKe, a community-based e-commerce application, was developed to address these issues by providing an integrated, accessible, and community-based marketing solution. The research methodology includes analyzing UMKM needs through surveys and interviews, developing the application using an iterative approach, and testing and evaluating the platform's effectiveness. The initial stage of the research involved an in-depth analysis of the needs and challenges faced by UMKM in West Sulawesi. The analysis results indicated that the majority of UMKM have limitations in market access and digital technology usage. Based on these findings, the DiKe application was developed, offering features such as online store creation, social media integration, and analytics tools for sales performance monitoring. The application trial was conducted for six months involving 50 UMKM as respondents. Effectiveness evaluation was done by measuring changes in sales, market reach, and user satisfaction. The study results show that the use of the DiKe platform significantly increased the market reach and sales of UMKM products. About 85% of users reported increased sales with an average increase of 30%. Additionally, 90% of users stated that this application made it easier for them to conduct digital marketing, especially in terms of product promotion and customer interaction. Furthermore, interactions and collaborations among community members also increased. The community features in the application allow users to share experiences, marketing tips, and engage in business collaborations, thereby creating a more solid ecosystem that supports local business growth. The study also found that UMKM actively participating in the community tend to experience higher business performance improvements compared to those that are not active. Thus, this community-based e-commerce platform has proven effective in supporting digital marketing for UMKM in West Sulawesi. This success indicates the potential for adoption in other regions with similar characteristics, thereby providing broader benefits for UMKM development nationally. This research significantly contributes to the literature on community-based e-commerce and offers a model that can be implemented in various regional contexts.